A study of applying severity-weighted greedy algorithm to software test case prioritization during testing - Hsu, Yen-Ching; Peng, Kuan-Li; Huang, Chin-Yu (2014 IEEE International Conference on Industrial Engineering and Engineering Management, 2014)
Regression testing is a very useful technique for software testing. Traditionally, there are several techniques for test case prioritization; two of the most used techniques are Greedy and Additional Greedy Algorithm (GA and AGA). However, it can be found that they may not consider the severity while prioritizing test cases. In this paper, an Enhanced Additional Greedy Algorithm (EAGA) is proposed for test case prioritization. Experiments with eight subject programs are performed to investigate the effects of different techniques under different criteria and fault severity. Experimental results show that proposed EAGA perform well than other techniques.